Corporate governance and corporate creditworthiness - Dror Parnes (Journal of Risk and Financial Management, 2011)
We examine the relation between corporate governance and bankruptcy risk as an underlying force affecting a bond's yield. The level of corporate governance is captured by the G-index, along with the explicit groups of governance provisions. We estimate bankruptcy risk by Z-score, by cash-flow-score, by O-score, through Merton structural model default probabilities, and by S&P credit ratings. After addressing endogeneity and while controlling for firm-specific factors, based on the four objective methodologies we find that corporate governance is inversely related to bankruptcy risk. Yet, rating agencies take a mixed approach towards this association likely because of the conflicting impact of different governance provisions.
Keywords: G33; G34; 330; Corporate Governance; Bankruptcy Risk; G-index; Endogeneity Tests; Corporate Governance Provisions